Task System of Payment for Soil Conservation Works - Murty, V.V.N (Journal of Soil and Water Conservation, 2022)
Execution of soil conservation works on a large scale require considerrable planning and ianpower. In the execution of all the soil conservation works employment of manual labour is necessary and only in a very few cases machinery is employed. These workers engaged are only unskilled and with little instruction they will be able to perform the job satisfactorily. At present in our country large scale soil conservation works are carried out by Govt. Departments. It is obligatory on the part of these executing agencies to see that the workers engaged get due wages for the work turned out by them and at the same time proper amount of work of proper quality is got done. This is an important factor when we consider that soil conservation works not only help in land improvement but at the same time are useful for providing employment for idle rural manpower, landless agricultural labourers, regular labour force depending upon employment, or as famine relief works. Viewed in this perspective it is the responsibility of the executive officers to see that the wages are received directly by the labourers without any middle Than getting undue advantage.